PENGARUH GCG, FREE CASH FLOW, INDEPENDENSI AUDITOR DAN PROFITABILITAS TERHADAP MANAJEMEN LABA - Hustianto Sudarwadi (Fakultas Ekonomi dan Bisnis, Universitas Papua., 2021)
This study aims to examine the effect of Good Corporate Governance, Free Cash Flow, Auditor Independence and Profitability on Earnings Management. Good Corporate Governance is measured using the number of members, Free Cash Flow is measured using free cash flow, Auditor Independence is measured using the length of audit assignment in a company, Profitability is measured using the ROA formula, and Earnings Management is measured using the modified Jones model. The population in this study is the financial statements of manufacturing companies listed on the Indonesia Stock Exchange for the 2016-2018 period. The sampling technique used a probability sampling technique in the form of simple random sampling with a total sample of 191 financial statements. The analysis used in this study was multiple linear regression analysis which was processed using the SPSS version 22 program. The results showed that Good Corporate Governance and Free Cash Flow had no effect on earnings management, while Auditor Independence and Profitability had an effect on Earnings Management.